Model for Post-Pandemic Bureaucracy in Indonesia: Is Post-Bureaucracy Relevant? - Dodi Faedlulloh; Yulianto Yulianto (Jurnal Borneo Administrator, 2023)
This research aims to investigate alternative post-pandemic bureaucratic models. This research contributes to the theoretical and practical knowledge of appropriate bureaucratic models during the pandemic and its aftermath. This research employed a qualitative method with a constructivist approach through a comprehensive literature review from credible sources, including scientific journals, books, and information from official government websites or international institutions. The results show that post-bureaucracy can be an antithesis and alternative to Indonesia's dominant Weberian bureaucratic paradigm. While the Weberian bureaucracy relies on rigid rules and structures, post-bureaucracy thrives on flexibility, citizencenteredness, open organizational boundaries, and a focus on people. These postbureaucratic characteristics are particularly relevant to the Indonesian context. The practical implication is that the Indonesian government needs to consider the postbureaucratic model to initiate a transformative change in bureaucracy in response to the evolving challenges posed by the pandemic and its aftermath.